Role of supplementary feeding in reindeer husbandry - Åhman, Birgitta; Turunen, Minna; Kumpula, Jouko; Risvoll, Camilla; Horstkotte, Tim; Lépy, Élise; Eilertsen, Svein Morten (2022)
The chapter discusses the practice of providing reindeer with supplementary feed in winter as part of reindeer husbandry in Finland, Sweden and Norway. It describes how feeding is practised, and the benefits and problems connected with this practice, as perceived in the scientific literature and by herders. It also reflects on the possible future role of feeding. Feeding of reindeer is more common in Finland than in the other two countries but seems to be gradually increasing across all Fennoscandia. The main reason is the continuing loss and deterioration of winter pastures due to expanding land use by forestry, mineral and energy production and other industrial and infrastructure schemes, leading to increased grazing pressure on the remaining land. Climate change increases the frequency of difficult winter grazing conditions, and growing predator populations restrict the use of pastures for reindeer grazing. Reduced access to natural pasture can be counteracted by supplementary feeding, but at high costs and risks of impaired animal health and welfare. Herders are also concerned that increased use of feeding may threaten land rights, transfer of traditional knowledge between generations and the ability of reindeer to make use of natural pasture resources, and thereby the traditional management system as a whole.